Phonon spectroscopy with chirped shear and compressive acoustic pulses - Poyser, Caroline Louise; York, W.B.; Srikanthreddy, D.; Glavin, B.A.; Linnik, T.L.; Campion, R.P.; Akimov, A.V.; Kent, A.J. (American Physical Society, 2017)
Picosecond duration compressive and shear phonon wave packets injected into (311) GaAs slabs transform after propagation through ∼1  mm into chirped acoustic pulses with a frequency increasing in time due to phonon dispersion. By probing the temporal optical response to coherent phonons in a near surface layer of the GaAs slab, we show that phonon chirping opens a transformational route for high-sensitivity terahertz and subterahertz phonon spectroscopy. Temporal gating of the chirped phonon pulse allows the selection of a narrow band phonon spectrum with a central frequency up to 0.4 THz for longitudinal and 0.2 THz for transverse phonons.